Interior of IBM Pavilion
Caption, "World's Fair, N.Y. Visitors at the IBM New York World's Fair Pavilion participate in a demonstration of two computer accomplishments recognition of handwritten characters and information retrieval. An optical scanning device reads a date written on a card by visitors and retrieves a featured headline published by the New York Times on that date. The recognized number is transmitted to and IBM 1460 data processing system where nearly 40,000 headlines from the Times are stored."